Characterization of Monoclonal Anti-human Factor VII Antibody (B101/B1) that Recognized Three-dimensional Structures near Arg at Position 79 in the First EGF-like Domain - Takamiya, Osamu (Thrombosis and Haemostasis, 1998)
Murine monoclonal antibodies (designated hVII-B101/B1, hVIIDC2/D4 and hVII-DC6/3D8) directed against human factor VII (FVII) were prepared and characterized, with more extensive characterization of hVII-B101/B1 that did not bind reduced FVIIa. The immunoglobulin of the three monoclonal antibodies consisted of IgG1. These antibodies did not inhibit procoagulant activities of other vitamin K-dependent coagulation factors except FVII and did not cross-react with proteins in the immunoblotting test. hVII-DC2/D4 recognized the light chain after reduction of FVIIa with 2-mercaptoethanol, and hVIIDC6/3D8 the heavy chain. hVII-B101/B1 bound FVII without Ca2+, and possessed stronger affinity for FVII in the presence of Ca2+. The Kd for hVII-B101/B1 to FVII was 1.75 x 10–10 M in the presence of 5 mM CaCl2. The antibody inhibited the binding of FVII to tissue factor in the presence of Ca2+. hVII-B101/B1 also inhibited the activation of FX by the complex of FVIIa and tissue factor in the presence of Ca2+. Furthermore, immunoblotting revealed that hVII-B101/B1 reacted with non-reduced γ-carboxyglutaminic acid (Gla)-domainless-FVII and/or FVIIa. hVII-B101/B1 showed a similar pattern to that of non-reduced proteolytic fragments of FVII by trypsin with hVII-DC2/D4 on immunoblotting test. hVII-B101/B1 reacted differently with the FVII from the dysfunctional FVII variant, FVII Shinjo, which has a substitution of Gln for Arg at residue 79 in the first epidermal growth factor (1st EGF)-like domain (Takamiya O, et al. Haemosta 25, 89-97,1995) compared with normal FVII, when used as a solid phase-antibody for ELISA by the sandwich method. hVII-B101/B1 did not react with a series of short peptide sequences near position 79 in the first EGF-like domain on the solid-phase support for epitope scanning. These results suggested that the specific epitope of the antibody, hVII-B101/B1, was located in the three-dimensional structure near position 79 in the first EGF-like domain of human FVII.